ANALISIS STRUKTUR DAN NILAI KEARIFAN LOKAL DALAM CERITA RAKYAT PERANG OBOR DI DESA TEGALSAMBI JEPARA - Mely Rohmawati; Tika Aniffartur Rif’ah; Siska Nadia Febrianti; Syaharani Naswa Natasya; Mohammad Kanzunnudin (Universitas Batanghari, 2024)
This research was designed to analyze the structure and value of local wisdom contained in the folklore